Canadian Metadata Catalogue for Health Science Research - Garland, Allan; Dodek, Peter; Thavorn, Kednapa; Wissa, Rita; Sligl, Wendy; Marleau, Wynona; Wilcox, Mary; Fortier, Isabel; for the Sepsis Canada Network (International Journal of Population Data Science, 2026)
Introduction While Canada is rich in databases useful to support healthcare research, they are widely distributed, often poorly documented, and it is challenging to identify relevant databases, apply for access, and eventually use, link or harmonise the data. Even if the databases needed to address specific questions are known, it is difficult and time-consuming to find the metadata, the ``data about the data'' required to understand the characteristics and data content of these resources. A solution to these challenges is creation of metadata catalogues, which detail metadata for multiple databases, not the actual data. Objectives Describe a new catalogue including metadata about Canadian medical and non-medical databases' characteristics and variables, and information to assist catalogue users in seeking data access. Methods Starting with a list of 385 national, provincial and regional databases, a group of physician-investigators, epidemiologists, data scientists and patient partners prioritised databases for inclusion. Metadata cataloguing occurred in steps: (i) description of the database with listing of its characteristics, and when available, (ii) addition of information about collected variables. Results 83 individual databases are documented in the Metadata Catalogue of the Sepsis Canada Network (https://www.maelstrom-research.org/network/sepsis). 57 are registries, 13 are cohort and 13 cross-sectional databases. 16 cover all of Canada, while another 13 cover most of the country; 45 focus on a single province. For 33 databases (38%) the catalogue includes detailed information about variables collected. Conclusions This metadata catalogue includes databases collecting information spanning the continuum of medical care, non-medical data, and determinants of health. It is freely available online and extensively searchable. It can facilitate implementation of a wide range of research initiatives into medical conditions, medical care, and outcomes.